MEDIA PEMBELAJARAN INTERAKTIF DALAM UPAYA MENDORONG PEMBELAJARAN BERPUSAT PADA SISWA DI SMA - Muhammad Iqbal Zabriliyan Putra; Yuniar Mujiwati; Muchammad Haidar Ali (STKIP Pesisir Selatan, 2026)
The advancement of information and communication technology has driven significant changes in learning practices at the senior high school (SMA) level, particularly in the shift from teacher-centered approaches to learning that places students at the center of the learning process (student-centered learning). One strategy considered relevant in supporting this transformation is the use of interactive learning media. This article aims to examine in depth the concept of interactive learning media, the characteristics of student-centered learning at the senior high school level, and the contribution of interactive learning media in promoting the implementation of student-centered learning. This study employs a qualitative approach through a literature review method by examining various scholarly sources, including academic journals, reference books, and relevant educational policy documents. The findings indicate that interactive learning media play a role in increasing student engagement, supporting independent learning and differentiated instruction, and providing fast and accurate feedback. Furthermore, interactive learning media are also able to create learning processes that are more collaborative, reflective, and meaningful for senior high school students.